Question:
Solution:
Consider the following functions:
![f(x)=\text{ 5x-3}](https://img.qammunity.org/2023/formulas/mathematics/high-school/x3d6f3pn29yczcxohqbrwxwko7vsojx8yp.png)
and
![g(x)=x^2-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/tjnjlmdgxyxqhaqggnuse2pq3l5nzyrt5i.png)
a) f(-3):
if we evaluate the function f at x = -3, we get:
![f(-3)=\text{ 5(-3)-3}=\text{ -15-3= -18}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cf8ygee9do58kjnsspfgg2jailf3b46qe4.png)
so that, the correct answer is:
![f(-3)=\text{ -18}](https://img.qammunity.org/2023/formulas/mathematics/high-school/lvkc8ey9qwh0jb1ynvjojen7hj4vuez8hr.png)
b) g(4):
if we evaluate the function g at x = 4, we get:
![g(4)=4^2-2=\text{ 16-2= 14}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1qmp3ddhggpx33bihbuc4zj46zw4hq876y.png)
so that, the correct answer is:
![g(4)=\text{ 14}](https://img.qammunity.org/2023/formulas/mathematics/high-school/c0xv9rzilnq1dtwojh5g36yvywm1qx9le9.png)
c) f(3)*g(3):
Step 1: evaluate f at x = 3:
![f(3)=\text{ 5(3)-3}=\text{ 15-3 = 12}](https://img.qammunity.org/2023/formulas/mathematics/high-school/gama4fi35ycgbm37utrujmkbcpp1o98nd2.png)
Step 2: evaluate g at x = 3:
![g(3)=3^2-2=\text{ 9-2= 7}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2actp6ijf8d2eq48d2ht6cvsentkmk5f6o.png)
Step 3: multiply f(3) and g(3):
![f(3)g(3)=\text{ (12)(7)=84}](https://img.qammunity.org/2023/formulas/mathematics/high-school/qr0cklg8pwqeghv9tmzcojo81duwzgl6x2.png)
so that, we can conclude that the correct answer is:
![f(3)g(3)=\text{84}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8j5dxmw0sbbebo5ub0jm5aohimx3czxxg5.png)